2016
DOI: 10.1002/14651858.cd002201.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids for cystic fibrosis

Abstract: Analysis 1.5. Comparison 1 Omega-3 fatty acids versus placebo, Outcome 5 Biochemical markers of essential fatty acid status (B4/B5 ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Correlations between altered FA levels and genotype, pancreatic status, and respiratory deficiency have been previously reported in CF subjects (Strandvik et al, 2001; Coste et al, 2008; Maqbool et al, 2008; Rise et al, 2010), and evidence has also been provided that a prolonged n-3 FA supplementation may have some positive effects on CF (Oliver and Watson, 2016). In our study, DHA supplementation resulted in a decrease of pro-inflammatory mediators, such as LTB 4 , suggesting that the lower concentrations of DHA observed in CF subjects (Rise et al, 2010) could indeed cause a lack of anti-inflammatory/pro-resolving LMs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Correlations between altered FA levels and genotype, pancreatic status, and respiratory deficiency have been previously reported in CF subjects (Strandvik et al, 2001; Coste et al, 2008; Maqbool et al, 2008; Rise et al, 2010), and evidence has also been provided that a prolonged n-3 FA supplementation may have some positive effects on CF (Oliver and Watson, 2016). In our study, DHA supplementation resulted in a decrease of pro-inflammatory mediators, such as LTB 4 , suggesting that the lower concentrations of DHA observed in CF subjects (Rise et al, 2010) could indeed cause a lack of anti-inflammatory/pro-resolving LMs.…”
Section: Discussionmentioning
confidence: 83%
“…COPD subjects, GOLD stage 2 to 3 under treatment according to the GOLD document (Vogelmeier et al, 2017), were examined at the time of enrolment, whereas CF patients were examined both at enrolment; after 10 weeks of supplementation with Aladin ® 500 mg (Laborest, Italy), two capsules, three times a day; and after an additional 10 weeks of washout. Dosage and duration regimen adopted were those already routinely used by the CF hospital unit, and were based on average values present in the literature (Coste et al, 2007; Oliver and Watson, 2016). Nine CF patients (five female) completed the study.…”
Section: Methodsmentioning
confidence: 99%
“…85 Acid suppressive drugs and broad spectrum antibiotics have been proposed and empirically employed to optimize fat absorption. 85 Despite insufficient evidence to draw firm conclusions, regular administration of omega 3 long-chain fatty acids 86 has also been proposed as beneficial in patients with CF. An approach to inadequate clinical response to PERT is suggested to the reader in Figure 1.…”
Section: Diagnosis Of Pimentioning
confidence: 99%
“…33 This turned all interest to this fatty acid resulting in many clinical studies supplementing DHA to patients with CF, but the results were mainly disappointing regarding any influence on the symptomatology. 34 Later a long-term study of similar cftrÀ/À mouse strain could not repeat the beneficial effect of DHA supplementation, but showed a protection of liver abnormality. 35 The development of murine models opened a possibility to study organ pathophysiology in CF, but the investigations have shown different results depending on models with null alleles or those with more or less CFTR function related to mutation strategy.…”
Section: Impact Statementmentioning
confidence: 99%